Migrant construction workers' demography and job satisfaction: a New Zealand study - Rotimi, James Olabode Bamidele; Ramanayaka, Chamil Erik; Olatunji, Oluwole Alfred; Rotimi, Funmilayo Ebun (Emerald, 2021)
Purpose: The demand for construction-related occupations has increased consistently over many years in New Zealand (NZ). This has necessitated recourse to migrant workers to address capacity and capability requirements. Migrant construction workers hail from various backgrounds with a complex set of their needs being met through employment in NZ. Research on understanding the satisfaction levels of this category of construction workers is scarce. With recent insinuations about migrant exploitations, research investigations into this knowledge area are significant. In this study, the authors sought to establish the moderating effect of migrants' demography on the determinants of job satisfaction in NZ's construction sector.